“Soft-Balancing”: Latin American Perspectives - Carranco Paredes, Santiago (2018)
The balance of traditional power and the Soft-Balancing are terms developed in northwestern schools. For this reason their conception depend on the condition and worldview of first world people. It is true that Latin American schools of International Relations have been founded on northwestern epistemological basis, however, these have developed in a different way since the behavior of a developing country is not the same as that of a developed one, thus the understanding of international matters may be different from the one that classic or neoclassic authors have. In other words, the comprehension of the balance of power ?s concept will determine the global conception of the matters that concern the international relations, depending on the school with which it is studied. Therefore, Soft-Balancing concept may be different from the original one of Robert Pape, when it is framed within a casethat happen outside the western world. Additionally, this difference may get bigger if such phenomena is studied by a Latin American researcher.